Role of Calcium Channels in Congenital Heart Block - Karnabi, Eddy (2010)
Congenital heart block (CHB) is a conduction abnormality that affects hearts of fetuses and/or newborn to mothers with autoantibodies reactive with the intracellular soluble ribonucleoproteins 48kD La, 52kD Ro, and 60kD Ro. CHB carries substantial mortality and morbidity, with more than 60% of affected children requiring lifelong pacemakers. Several hypotheses have been proposed to explain the pathogenesis of CHB. These can be grouped under three main hypotheses: Apoptosis, Serotoninergic and Ca channel hypothesis. Here we discuss these hypotheses and provide recent scientific thinking that will most likely dominate the future of this field of research.